¨Análisis HOSTING CAPACITY en los alimentadores de la subestación salcedo de ELEPCO S.A. para la inserción de paneles fotovoltaicos¨ - Gutierrez Calero, Klever Fabian (2021)
The progressive growth of distributed generation and technological advance, lead to various studies to be carried out to take advantage of the type of generation and in turn contribute to caring for the environment, in this case the research will be focused on the analysis of accommodation capacity that can be had in a distribution network, for which the voltage profile and the losses that exist in the system must be known, for our case study the evaluation of the electrical parameters is carried out in the model of the 13 bars of the IEEE with the help of the Open DSS software, once these parameters are known, their correct corrections can be established by inserting photovoltaic generation until the maximum limit available to the suppliers is determined and without affecting the existing parameters in the system, developed this base model the entire trajectory of feeder 3 of the Salcedo substation will be executed, where from the same In a better way, it will be possible to determine voltage profiles, losses before and after the insertion of photovoltaic generation and so, be able to determine the accommodation capacities available at each of the points of the distribution network. In addition, we will consider that the loads are residential and of type B as established by the Quito Electric Company and the type of panel to be used will be polycrystalline due to its technical characteristics